2016
DOI: 10.15405/epsbs.2016.11.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Work-Family Conflict among Nurses: A Qualitative Study

Abstract: Working women face stress due to the multiple roles they need to handle to achieve work and family life satisfaction when there is no full support from their spouses. Conflict will arise when they cannot balance their tasks at the workplace and their home. Nurses have many responsibilities in their workplace while needing to manage their families as well. Work-family conflict occurs when workplace responsibilities interfere with family life, such as inflexible working hours, work overload, interpersonal confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…However, most intern nurses in the intervention group reported suffering from value conflict between their family and work. In line with our findings, Sabil et al [ 20 ] reported that nurses had varying degrees of conflict while attempting to meet work expectations and family roles. Similarly, Guille et al [ 35 ] surveyed 3121 interns from 44 medical schools in the United States during the 2015–2016 academic year.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, most intern nurses in the intervention group reported suffering from value conflict between their family and work. In line with our findings, Sabil et al [ 20 ] reported that nurses had varying degrees of conflict while attempting to meet work expectations and family roles. Similarly, Guille et al [ 35 ] surveyed 3121 interns from 44 medical schools in the United States during the 2015–2016 academic year.…”
Section: Discussionsupporting
confidence: 92%
“…Balancing work and family life is challenging and conflicting for any adult needing more psychological flexibility. Sabil et al [ 20 ] verified that when people begin to work, they struggle to balance jobs and family life. Combining work and family is beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Perawat adalah profesi yang membutuhkan derajat emosional, perawat diharapkan dapat menampilkan dan memberikan emosi yang menyampaikan rasa pedulinya, pengertian dan empati terhadap pasiennya (Nik Safiah, dalam Sabil et al, 2016). Perawat merupakan profesi yang jenis pekerjaannya memberikan pelayanan dalam hal kesehatan kepada orang lain.…”
Section: Aunclassified
“…Similar to other countries, work characteristics have been found to crucially influence work-family conflict among nurses in Malaysia. A recent qualitative study by Sabil, Abu, Kasuma, and Lizzan (2016) suggested that shift work is one of the main factors affecting work-family conflict among nurses in the public hospitals. In another study, Nurumal et al (2017) reported that working in fixed shifts significantly affected nurses' work-life balance, unlike those working in rotational or multiple shifts.…”
Section: A Shift Workmentioning
confidence: 99%